Clinical presentation and long‐term outcomes of infantile hypertrophic cardiomyopathy: a European multicentre study. (6th September 2021) - Norrish, Gabrielle; Kolt, Gali; Cervi, Elena; Field, Ella; Dady, Kathleen; Ziółkowska, Lidia; Olivotto, Iacopo; Favilli, Silvia; Passantino, Silvia; Limongelli, Giuseppe; Caiazza, Martina; Rubino, Marta; et al.
Abstract: Aims: Children presenting with hypertrophic cardiomyopathy (HCM) in infancy are reported to have a poor prognosis, but this heterogeneous group has not been systematically characterized. This study aimed to describe the aetiology, phenotype, and outcomes of infantile HCM in a well‐characterized multicentre European cohort. Methods and results: Of 301 children diagnosed with infantile HCM between 1987 and 2019 presenting to 17 European centres [male n = 187 (62.1%)], underlying aetiology was non‐syndromic ( n = 138, 45.6%), RASopathy ( n = 101, 33.6%), or inborn error of metabolism (IEM) ( n = 49, 16.3%). The most common reasons for presentation were symptoms ( n = 77, 29.3%), which were more prevalent in those with syndromic disease ( n = 62, 61.4%, P < 0.001), and an isolated murmur ( n = 75, 28.5%). One hundred and sixty‐one (53.5%) had one or more co‐morbidities. Genetic testing was performed in 163 (54.2%) patients, with a disease‐causing variant identified in 115 (70.6%). Over median follow‐up of 4.1 years, 50 (16.6%) underwent one or more surgical interventions; 15 (5.0%) had an arrhythmic event (6 in the first year of life); and 48 (15.9%) died, with an overall 5 year survival of 85%. Predictors of all‐cause mortality were an underlying diagnosis of IEM [hazard ratio (HR) 4.4, P = 0.070], cardiac symptoms (HR 3.2, P = 0.005), and impaired left ventricular systolic function (HR 3.0, P = 0.028). Conclusions: This large, multicentre study of infantile HCM describes a complex cohort of patients with a diverse phenotypic spectrum and clinical course. Although overall outcomes were poor, this was largely related to underlying aetiology emphasizing the importance of comprehensive aetiological investigations, including genetic testing, in infantile HCM.